THE EVOLUTION OF POLITICAL CAMPAIGN TECHNIQUES: A LITERATURE REVIEW OF CHANGING STRATEGIES OVER TIME - Ben Brahim S. B.; Al-Amin (Adisam Publisher, 2025)
The evolution of political campaigning techniques is a reflection of technological developments and shifting communication practices in society. This literature study explores how campaign strategies have changed historically from the use of print media and traditional face-to-face communication to the utilisation of sophisticated digital tools in the modern era. The results show that the evolution of political campaign techniques emphasises the importance of transparency, fair regulation and media education to ensure that technological advances enrich rather than disrupt the integrity of democratic practices and electoral processes.